EFEK ASAP BAKARAN SATE TERHADAP JUMLAH RETIKULOSIT PADA PEDAGANG SATE DI KECAMATAN WIRADESA KABUPATEN PEKALONGAN - Suparyati Suparyati (LPPM Universitas Pekalongan, 2021)
One of the jobs with a risk of exposure to gas for a long time is satay traders. Smoke in the process of burning satay contains carbon dioxide (CO2), hydrogen (H2), hydrocarbons (CH4), and carbon monoxide (CO). Carbon monoxide has an affinity for hemoglobin 200 times that of O2 for hemoglobin. Carbon monoxide (CO) from combustion is hazardous if it enters the body through the air, which directly impacts hemoglobin and automatically affects human reticulocytes. Increased reticulocyte and erythrocyte counts can be bad for health. The purpose of this study was to determine the effect of smoked satay burnt on the number of reticulocytes in satay traders in Wiradesa District, Pekalongan Regency. The research method used is cross-sectional, namely taking samples at one time on satay traders exposed to smoke from the satay burning process and counting the number of reticulocytes. The population is 20 with the sampling technique using total sampling so that the sample in this study is 20 samples from 20 populations. The results showed that of the 20 samples examined, the number of reticulocytes was less than normal as many as seven samples (35%), the number of normal reticulocytes was four samples (20%), and the number of reticulocytes was more than normal nine samples (45%). Conclusion: From the results of the examination, count the number of reticulocytes in satay traders who exposed to smoke from the satay burning process has a reticulocyte count increased.